2017
DOI: 10.1007/978-3-319-72817-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Multistage Downstream Attack Detection in a Cyber Physical System

Abstract: Abstract. We present an attack detection scheme for a water treatment system. We leverage the connectivity of two stages of the process to detect attacks downstream from the point of attack. Based on a mathematical model of the process, carefully crafted and executed attacks, are detected by deploying CUSUM and Bad-Data detectors. Extensive experiments are carried out and the results show the performance of the proposed scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Therefore, any validation must be carried out in a strictly controlled environment to avoid accidental disruption to CNI or compromise to data privacy. Validation can be economically challenging and requires funding to facilitate validations using a realistic simulation environment often involving physical infrastructure [47,51,64,109,119,131,137,142]. Almost three-quarters of the primary studies reported funding supported by research grants, defence or governmental sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any validation must be carried out in a strictly controlled environment to avoid accidental disruption to CNI or compromise to data privacy. Validation can be economically challenging and requires funding to facilitate validations using a realistic simulation environment often involving physical infrastructure [47,51,64,109,119,131,137,142]. Almost three-quarters of the primary studies reported funding supported by research grants, defence or governmental sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in their subsequent work [2] they designed a distributed mechanism for detecting cyber attacks on a water treatment system by systematically deriving invariants. Recently, in [6,7,30,33] researchers report an investigation into the effectiveness of yet another detection scheme that uses the Kalman filter on an operational water treatment testbed system. Experimental investigation on operational and real testbeds provides how an attacker can perform attacks on these systems to achieve his goal.…”
Section: Related Workmentioning
confidence: 99%
“…Stealthy Attacks(S7): An attacker modifies a sensor measurement and attempts to hide it's presence. In the literature [37], [45], [48], [49], [50] specific stealthy attacks have been designed to stay undetected for a range of statistical detectors. To achieve the stealthiness an attacker must modify sensor measurement in a way so that it can maximize the damage and remain undetected.…”
Section: Physical (Analog Domain) Attacksmentioning
confidence: 99%